On an Optimal Linear Control Applied to a Non-Ideal Load Transportation System, Modeled with Periodic Coefficients - Chavarette, Fábio Roberto [UNESP]; Peruzzi, Nelson José [UNESP]; Balthazar, José Manoel [UNESP]; Barbanti, Luciano [UNESP]; Damasceno, Berenice Camargo [UNESP] (Trans Tech Publications Ltd, 2011)
In this paper, a load transportation system in platforms or suspended by cables is considered. It is a monorail device and is modelled as an inverted pendulum built on a car driven by a DC motor. The governing equations of motion were derived via Lagrange's equations. In the mathematical model we consider the interaction between the DC motor and the dynamical system, that is, we have a so-called non-ideal periodic problem. The problem is analysed and we also developed an optimal linear control design to stabilize the problem.
Keywords: Optimal Linear Control; Non-Ideal System; Transportation System